Airway molecular endotypes of asthma. Issue 2 (April 2015) - Wesolowska-Andersen, Agata; Seibold, Max A.
<x xml:space="preserve">Abstract</x> Purpose of review This review will cover advances over the past year in defining airway endotypes in asthma by gene expression and the relationship between these endotypes and clinical traits. Recent findings Expression profiling studies of asthmatic airway samples continue to reveal significant heterogeneity in airway inflammation and dysfunction. Recent studies have indicated multiple distinct, but related Th2 inflammatory asthma endotypes. Moreover, novel biomarkers of Th2 inflammation are being identified in more accessible nasal brushing and induced sputum cell samples. New data suggest the presence of multiple non-Th2-driven asthma molecular endotypes, including ones related to neutrophilic inflammation, airway remodeling, and chemosensory dysfunction. Many of these endotypes are associated with clinical disease features and treatment response. Summary Molecular endotyping of asthmatic patients using gene expression profiling of airway samples is helping to uncover disease mechanisms and potential novel treatment targets. The advancement of endotyping methods holds the promise of future personalized treatment for asthma.